2012
DOI: 10.1210/en.2012-1396
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Activation Induces Peptide YY Transcription in Pancreatic Islets

Abstract: Peptide YY (PYY) is a peptide hormone secreted from L cells in the intestine after food intake and regulates appetite and intestinal function. PYY is also expressed in the pancreas, but the mechanisms of regulation of pancreatic PYY expression have not been elucidated. The vitamin D receptor (VDR) is a nuclear receptor for the active form of vitamin D(3) and regulates numerous physiological processes. Because VDR is expressed in the pancreas, we investigated the role of pancreatic VDR activation and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…The PYY can be stimulated by intraluminal nutrients, including glucose, bile salts, lipids, short-chain fatty acids and amino acids [31]. Our results showed that dietary pyridoxine decreased PYY gene expression in duodenum, which is inconsistent with lipid-soluble vitamins-treated experiment that vitamin D increased circulating protein levels of PYY [32]. Coll et al [28] has proved that the anorexia effect of PYY was initially thought to be mediated through the central melanocortin system.…”
Section: Discussioncontrasting
confidence: 55%
“…The PYY can be stimulated by intraluminal nutrients, including glucose, bile salts, lipids, short-chain fatty acids and amino acids [31]. Our results showed that dietary pyridoxine decreased PYY gene expression in duodenum, which is inconsistent with lipid-soluble vitamins-treated experiment that vitamin D increased circulating protein levels of PYY [32]. Coll et al [28] has proved that the anorexia effect of PYY was initially thought to be mediated through the central melanocortin system.…”
Section: Discussioncontrasting
confidence: 55%
“…Choi et al showed that vitamin D indirectly increased the expression of the PYY hormone gene in the pancreas of mice. They showed that vitamin D supplementation increases the expression of vitamin D receptor genes in the pancreas and VDR activation induces peptide YY transcription in pancreatic islets (27). Regarding the effect of vitamin D supplementation on weight loss, BMI and body fat percentage, there is no research to show that vitamin D alone causes weight loss, decreased BMI and body fat percentage, but researchers have found a link between serum vitamin D levels and these variables.…”
Section: Discussionmentioning
confidence: 99%
“…These adjustments are made through the transcription pathways of the Neuropeptide Y (NPY) or Agouti related protein (AgRP) (24,25). Vitamin D supplementation increases the expression of vitamin D receptor (VDR) gene in the pancreas (26), and VDR activation induces peptide YY transcription in pancreatic islets (an appetite suppression hormone that is produced in the pancreas in addition to intestinal L cells) (27). Daily intake of vitamin D supplements can maintain a sufficient serum level (above 30 ng/ml), but the daily dose varies according to age, gender, geographical location, skin pigmentation, physical activity and season.…”
Section: Introductionmentioning
confidence: 99%
“…cDNAs were synthesized from total RNA samples with the ImProm‐II reverse transcription system (Promega Corporation, Madison, WI, USA), and subjected to real‐time polymerase chain reaction with the ABI PRISM 7000 sequence detection system or the StepOnePlus Real‐time PCR system (Thermo Fisher Scientific) using Power SYBR Green PCR Master Mix (Thermo Fisher Scientific). All primer sequences were reported previously . The calculated RNA values were normalized with the Cyclophilin B (gene symbol Ppib ) or glyceraldehyde‐3‐phosphate dehydrogenase ( Gapdh ) mRNA levels.…”
Section: Methodsmentioning
confidence: 99%